Tourism, subsidy and hotel supply. The commemoration of the IV Centenary of the Spanish Foundation of Cuzco (1934) - Loayza Velásquez, Santiago (2023)
The objective of this study is to identify the various uses given to the extraordinary grant provided by the Peruvian Government to the commission responsible for commemorating the IV Centenary of the Spanish Foundation of the city of Cusco. Additionally, it aims to analyze the conflicts that arose among local elites over the use of this grant. The hypothesis posits that the grant encouraged local leaders to undertake projects that resulted in favorable changes in the urban and economic composition of the city, but simultaneously fueled conflicts among Cusco’s elites, who sought larger percentage allocations for execution in their respective sectors. As a result, subcommittees were established to carry out works in support of Cusco’s tourist image. The research draws on bibliographic materials, documents preserved in the Historical Archive of the Municipal Library of Cusco (AHBMC), and publications in the El Comercio de Cusco newspaper (ECC). The funds allocated contributed to actions that led to favorable conditions in the city of Cusco and its tourist image, creating an atmosphere of progress and fostering entrepreneurial spirit in the hotel industry sector.